Ipad application development for dummies - Goldstein, Neal [ (Neal D.)]; Bove, Tony , 1955- (--For dummies, 2011)
Provides information on creating applications for the iPad, covering such topics as using Xcode, becoming a registered developer, working with the multi-touch interface, and submitting and selling apps in the App Store